Pseudo-capacitance reinforced modified graphite for fast-charging potassium-ion batteries. (15th November 2021) - Yuan, Fu; Lei, Yu; Wang, Huwei; Li, Xiaojing; Hu, Junyang; Wei, Yaojie; Zhao, Rongyi; Li, Baohua; Kang, Feiyu; Zhai, Dengyun
Abstract: As emerging energy storage systems, potassium-ion batteries (PIBs) are suitable for grid-scale energy storage application due to the abundant potassium resources and low cost. It is crucial to achieve fast-charging PIBs. However, as the most promising anode candidate, graphite still faces setbacks in achieving fast charging due to poor kinetic issue. Herein, modified graphite (MG) is synthesized to realize the fast potassium ion storage. Benefiting from the enlarged graphitic space combined with unique porous microstructure, MG exhibits outstanding electrochemical performance. The optimized MG anode delivers a specific capacity of 115 mAh g −1 at 4 A g −1 and excellent cycling stability of 1500 cycles at 1 A g −1 . Moreover, the full cell assembled with MG anode and Prussian Blue (PB) cathode exhibits a capacity retention of 75% after 20000 cycles at the current density of 1 A g −1 . The excellent electrochemical performance is further demonstrated to be associated with dominant pseudo-capacitance behavior, i.e. surface or near-surface reversible redox reactions, which are less affected by solid electrolyte interface (SEI) than intercalation reactions. Our work proposes a strategy to optimize graphitic anode materials by regulating the microstructure and may provide insight into the synthesis of high rate carbon-based anode materials for PIBs. Graphical abstract: A low-cost modified graphite (MG) is prepared as an anode for potassium-ion batteries (PIBs), achieving higher specific capacity and superior long-term cyclic stability than pristine natural graphite. Moreover, the different impact of solid electrolyte interface (SEI) accumulation during K storage on the two K storage mechanisms (intercalation and adsorption mechanism) is investigated. Image 1 Highlights: A low-cost modified graphite was prepared as an anode to achieve fast-charging K-ion battery. The first attempt to illustrate different impact of SEI on intercalation and adsorption K storage mechanisms. Adsorption K storage mechanism is less affected by SEI than intercalation behavior.